2013
DOI: 10.1074/jbc.r113.462929
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant Sensing by Reversible Disulfide Bond Formation

Abstract: Maintenance of the cellular redox balance is crucial for cell survival. An increase in reactive oxygen, nitrogen, or chlorine species can lead to oxidative stress conditions, potentially damaging DNA, lipids, and proteins. Proteins are very sensitive to oxidative modifications, particularly methionine and cysteine residues. The reversibility of some of these oxidative protein modifications makes them ideally suited to take on regulatory roles in protein function. This is especially true for disulfide bond form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
275
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(284 citation statements)
references
References 100 publications
5
275
0
4
Order By: Relevance
“…inactivated phosphatases were hypothesized to shift the equilibrium of inactive to active kinases resulting in enhanced kinase activity (18,25,26). By now, a large number of redox modifications in phosphatases, kinases, adapters, receptors, and transcription factors have been proposed to modulate signaling, among them multiple components of the BCR signaling pathway such as tyrosine-protein kinase Lyn, tyrosine-protein kinase SYK (Syk), tyrosine-protein phosphatase nonreceptor types 6 and 11 (SHP1/PTPN6; SHP2/PTPN11), phosphatase and tensin homolog, and a mitogen activated protein (MAP) kinase serine/threonine phosphatase (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, it has been challenging to prove or disprove the physiological relevance of such a mechanism, and results have been difficult to reconcile as a whole (3,26,35).…”
mentioning
confidence: 99%
“…inactivated phosphatases were hypothesized to shift the equilibrium of inactive to active kinases resulting in enhanced kinase activity (18,25,26). By now, a large number of redox modifications in phosphatases, kinases, adapters, receptors, and transcription factors have been proposed to modulate signaling, among them multiple components of the BCR signaling pathway such as tyrosine-protein kinase Lyn, tyrosine-protein kinase SYK (Syk), tyrosine-protein phosphatase nonreceptor types 6 and 11 (SHP1/PTPN6; SHP2/PTPN11), phosphatase and tensin homolog, and a mitogen activated protein (MAP) kinase serine/threonine phosphatase (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, it has been challenging to prove or disprove the physiological relevance of such a mechanism, and results have been difficult to reconcile as a whole (3,26,35).…”
mentioning
confidence: 99%
“…ROS transiently modulate protein activity by protein modification, most commonly via the formation of disulfide bonds. [10][11][12] Recent studies suggest that thiol exchange pathways involving protein disulfide isomerase (PDI) regulate TF activation via reversible disulfide bond formation. [13][14][15][16] Wang et al 17 showed that thioredoxin (Trx) knockdown caused a significant increase in cell surface TF procoagulant activity in MDA-MB-231 cells, indicating that the thioredoxin reductase (TrxR)/Trx system negatively regulates TF coagulant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The redox state inside the ER lumen is highly oxidant and the changes caused by the presence of ROS afect the correct protein folding. It contributes to the breaking of the disulphide bonds by the binding of reactive species to thiol groups [51]. Misfolded proteins that are formed in the ER cause Ca 2+ release in the cytoplasmic space.…”
Section: Alterations In Endoplasmic Reticulum Function and Signalmentioning
confidence: 99%